Graha Maria Annai Velangkanni sebagai Bentuk Pewartaan Injil secara Inkulturatif di Medan - M. Marihot Simanjuntak (P3TK, Sanata Dharma University, 2019)
Marian Shrine of Annai Velangkanni, which is located in Sakura III Street Medan-North Sumatera, actually is a Catholic-church with Hindu-Moghul architecture. Many people visit this shrine because of its uniqueness, the ornaments and symbols, and the service of Fr. James Bharataputra, SJ. This building becomes a precious asset for the Archdiocese of Medan. The aim of this article is to prove the effectiveness of Marian Shrine of Annai Velangkanni for inculturated evangelization. How can the idea of the founder be understood by the visitors? How can evangelization, inculturation, and devotion be developed in the Archdiocese of Medan? These questions will be answered by a field-research. We use mixed method: qualitative and quantitative namely with depth interviews and questioner. In the light of Evangelii Gaudium, we would support, criticize, and suggest pastoral movements to develop Maria Shrine of Annai Velangkanni. The inculturation can be found in this shrine and become an effective evangelization. The management should be a system which involves many parts to give a better service and increase the inculturation with local cultures (Batak).